Transversus Abdominis Plane Block: An Updated Review of Anatomy and Techniques. (31st October 2017) - Tsai, Hsiao-Chien; Yoshida, Takayuki; Chuang, Tai-Yuan; Yang, Sheng-Feng; Chang, Chuen-Chau; Yao, Han-Yun; Tai, Yu-Ting; Lin, Jui-An; Chen, Kung-Yen
Abstract : Purpose of Review . Transversus abdominis plane (TAP) block is a regional technique for analgesia of the anterolateral abdominal wall. This review highlights the nomenclature system and recent advances in TAP block techniques and proposes directions for future research. Recent Findings . Ultrasound guidance is now considered the gold standard in TAP blocks. It is easy to acquire ultrasound images; it can be used in many surgeries involving the anterolateral abdominal wall. However, the efficacy of ultrasound-guided TAP blocks is not consistent, which might be due to the use of different approaches. The choice of technique influences the involved area and block duration. To investigate the actual analgesic effects of TAP blocks, we unified the nomenclature system and clarified the definition of each technique. Although a single-shot TAP block is limited in duration, it is still the candidate of the analgesic standard for abdominal wall surgery because the use of the catheter technique and liposomal bupivacaine may overcome this limitation. Summary . Ultrasound-guided TAP blocks are commonly used. With the unified nomenclature and the development of catheter technique and/or liposomal local anesthetics, TAP blocks can be applied more appropriately to achieve better pain control.